Negative dielectrophoretic capture of bacterial spores in food matrices - Koklu, Mehti (American Institute of Physics, 2010)
A microfluidic device with planar square electrodes is developed for capturing particles from high conductivity media using negative dielectrophoresis (n-DEP). Specifically, Bacillus subtilis and Clostridium sporogenes spores, and polystyrene particles are tested in NaCl solution (0.05 and 0.225 S∕m), apple juice (0.225 S∕m), and milk (0.525 S∕m). Depending on the conductivity of the medium, the Joule heating produces electrothermal flow (ETF), which continuously circulates and transports the particles to the DEP capture sites. Combination of the ETF and n-DEP results in different particle capture efficiencies as a function of the conductivity. Utilizing 20 μm height DEP chambers, “almost complete” and rapid particle capture from lower conductivity (0.05 S∕m) medium is observed. Using DEP chambers above 150 μm in height, the onset of a global fluid motion for high conductivity media is observed. This motion enhances particle capture on the electrodes at the center of the DEP chamber. The n-DEP electrodes are designed to have well defined electric field minima, enabling sample concentration at 1000 distinct locations within the chip. The electrode design also facilitates integration of immunoassay and other surface sensors onto the particle capture sites for rapid detection of target micro-organisms in the future.